How Do Investigation Experiences Shape Views of the Police? Qualitatively Exploring Sexual Assault Survivors’ Interactions With Police Detectives and Subsequent Views of the Police - Lorenz, Katherine (Crime & delinquency, 2023)
Little attention has been paid to views of the police among sexual assault survivors. Understanding views of the police among a large population of crime victims who have historically been silenced and mistreated by our criminal-legal system can help inform recent and ongoing conversations about police funding and criminal justice reform. Qualitative interview data from a community sample of sexual assault survivors explored how police-detective interactions during sexual assault investigations shape views of the police. Negative interactions led to negative views of the police and for some were based on a culmination of positive and negative experiences. I share recommendations for responding to sexual assault that consider sexual assault survivors? experiences with and views of the police.